Identification of a fibrinogen-related protein (FBN9) gene in neotropical anopheline mosquitoes - Oliveira, Sabrina Alberti Nóbrega de; Ibraim, Izabela Coimbra; Tadei, Wanderli Pedro; Ruiz, Jerônimo Conceição; Nahum, Laila Alves; Brito, Cristiana Ferreira Alves de; Moreira, Luciano Andrade (Malaria Journal, 2011)
Background: Malaria has a devastating impact on worldwide public health in many tropical areas. Studies on vector immunity are important for the overall understanding of the parasite-vector interaction and for the design of novel strategies to control malaria. A member of the fibrinogen-related protein family, fbn9, has been well studied in Anopheles gambiae and has been shown to be an important component of the mosquito immune system. However, little is known about this gene in neotropical anopheline species. Methods. This article describes the identification and characterization of the fbn9 gene partial sequences from four species of neotropical anopheline primary and secondary vectors: Anopheles darlingi, Anopheles nuneztovari, Anopheles aquasalis, and Anopheles albitarsis (namely Anopheles marajoara). Degenerate primers were designed based on comparative analysis of publicly available Aedes aegypti and An. gambiae gene sequences and used to clone putative homologs in the neotropical species. Sequence comparisons and Bayesian phylogenetic analyses were then performed to better understand the molecular diversity of this gene in evolutionary distant anopheline species, belonging to different subgenera. Results: Comparisons of the fbn9 gene sequences of the neotropical anophelines and their homologs in the An. gambiae complex (Gambiae complex) showed high conservation at the nucleotide and amino acid levels, although some sites show significant differentiation (non-synonymous substitutions). Furthermore, phylogenetic analysis of fbn9 nucleotide sequences showed that neotropical anophelines and African mosquitoes form two well-supported clades, mirroring their separation into two different subgenera. Conclusions: The present work adds new insights into the conserved role of fbn9 in insect immunity in a broader range of anopheline species and reinforces the possibility of manipulating mosquito immunity to design novel pathogen control strategies. © 2011 Oliveira et al; licensee BioMed Central Ltd.
Keywords: Amino Acid; Fibrinogen Related Protein 9; Insect Proteins; Nucleotide; Unclassified Drug; Fibrinogen; Immunoglobulin; Aedes Aegypti; Amino Acid Substitution; Anopheles; Anopheles Albitarsis; Anopheles Aquasalis; Anopheles Darlingi; Anopheles Marajoara; Anopheles Merus; Anopheles Nuneztovari; Anopheles Quadriannulatus; Bayes Theorem; Cladistics; Comparative Study; Controlled Study; Disease Carrier; Evolutionary Homology; Gene Identification; Gene Sequence; Genetic Variability; Genotype; Cloning, Molecular; Neotropics; Nonhuman; Nucleotide Sequence; Phylogeny; Sequence Homology; Polymorphism, Single Nucleotide; Amino Acid Sequence; Animals; Classification; Gene; Genetics; Immunology; Malaria; Evolution, Molecular; Parasitology; Sequence Analysis; Amino Acid Sequence; Animal; Anopheles; Base Sequence; Cloning, Molecular; Evolution, Molecular; Fibrinogen; Genes, Insect; Immunoglobulins; Insect Vectors; Malaria; Phylogeny; Sequence Analysis